Modifications of histone cores and tails in V(D)J recombination - Muegge, Kathrin (BioMed Central, 2003)
The organization of chromatin and modifications to the tails of histone proteins are thought to be important in regulating the rearrangement of V, D and J gene segments, which encode immunoglobulins and T-cell receptors. A recent study shows that methylated lysine 79 in the core region of histone H3 also plays a role by providing a euchromatic 'mark' that may regulate access of the V(D)J recombinase.